Framework for the implementation of advanced HIV disease diagnostics in sub-Saharan Africa: programmatic perspectives. Issue 7 (July 2020) - Ndlovu, Zibusiso; Burton, Rosie; Stewart, Rosanna; Bygrave, Helen; Roberts, Teri; Fajardo, Emmanuel; Mataka, Anafi; Szumilin, Elisabeth; Kerschberger, Bernhard; Van Cutsem, Gilles; Ellman, Tom
Summary: Patients with advanced HIV disease have a high risk of mortality, mainly from tuberculosis and cryptococcal meningitis. The advanced HIV disease management package recommended by WHO, which includes diagnostics, therapeutics, and patient psychosocial support, is barely implemented in many different countries. Here, we present a framework for the implementation of advanced HIV disease diagnostics. Laboratory and point-of-care-based reflex testing, coupled with provider-initiated requested testing, for cryptococcal antigen and urinary Mycobacterium tuberculosis lipoarabinomannan antigen, should be done for all patients with CD4 + cell counts of 200 cells per μL or less. Implementation of the advanced HIV disease package should be encouraged within primary health-care facilities and task shifting of testing to lay cadres could facilitate access to rapid results. Implementation of differentiated antiretroviral therapy delivery models can allow clinicians enough time to focus on the management of patients with advanced HIV disease. Efficient up-referral and post-discharge systems, including the development of patient-centric advanced HIV disease literacy, are also crucial. Implementation of the advanced HIV disease package is feasible at all health-care levels, and it should be part of the core of the global response towards ending AIDS as a public health threat.